Faktor-Faktor Yang Mempengaruhi Kualitas Laba Sebuah Studi Kajian Literatur - Rommel Togatorop; Carmel Meiden (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This research examines the influence audit quality in the context of audit practice. Audit quality plays a crucial role in ensuring the reliability of financial information presented by business entities. Therefore, a profound understanding of the factors influencing audit quality, including auditor competence, time and cost pressure, professional ethical standards, internal supervision and review, as well as regulations and standards, is essential for practitioners, regulators, and relevant stakeholders. This literature study summarizes previous research findings and explores the relationship between these factors and audit quality. The study was conducted by reviewing 13 previous studies related to audit quality, with articles from both within and outside Indonesia published between 2020 and 2023. The results are expected to provide insights into the impact of these factors on transparency and honesty in audited financial reporting, with potential implications for regulatory policies and business practices. The study highlights the importance of mitigating audit quality.